The Effect Of Family Ownership, Institutional Ownership, Managerial Ownership, Blockholder Ownership, And Board Of Directors On Company Performance - Manurung, Muhammad Rizqi Alriansyah; Wijaya, Juli Riyanto Tri (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2022)
This study aims to determine the effect of family ownership, institutional ownership, managerial ownership, blockholder ownership, and the board of directors on firm performance that is proxied by ROA (Return On Assets) in industrial companies related to consumer goods companies in the Indonesian Sharia Stock Index (ISSI) years 2015-2018. The sampling technique used was the purposive sampling technique in order to obtain a sample of 32 companies with 128 observations. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results showed the variable family ownership, and managerial ownership did not affect the firm company, while institutional ownership negatively affected firm performance. However, other variables namely blockholder ownership and the board of directors have a positive effect on firm performance.